THU0674 Rheumatic diseases and pregnancy: a single centre dedicated clinic experience. (12th June 2018) - Motta, F.; Ramoni, V.; Vitolo, B.; Milanesi, A.; Beneventi, F.; Quaglini, S.; Caporali, R.; Montecucco, C.
Abstract : Background: Pregnancy causes immune and endocrine systems alterations, therefore it can change the course of the rheumatic diseases. On the other hand, rheumatic diseases can negatively influence pregnancy outcome. Therefore, in the past pregnancy has been discouraged in patients with rheumatic diseases, for high maternal-fetal risks. Nowadays we are aware that counselling, planning of pregnancy, multidisciplinary management and follow up in a dedicated clinic are mandatory for a good maternal-fetal outcome. Objectives: To assess the impact of close multidisciplinay rheumatological-obstetrical management on high risk pregnancies. Methods: We considered patients diagnosed with a rheumatic disease before pregnancy who had at least one pregnancy prospectively followed at our dedicated clinic. Each patient underwent a monthly rheumatological and obstetrical evaluation during the all pregnancy. All obstetrical complications were recorded and a final pregnancy outcome was assessed: favourable outcome (delivery) or unfavourable outcome (spontaneous abortion/stillbirth/induced abortion). We then compared prospective versus anamnestic pregnancy outcomes. Results: Between 2005 and 2016, 862 women were evaluated. We included in the study 201 patients followed prospectively during 261 pregnancies. The patients were affected by 19 different rheumatic diseases, alone or in association. The most represented diagnoses were undifferentiated connective tissue disease (UCTD) (72 patients, 33.03%), rheumatoid arthritis (33, 15.14%), systemic lupus erythematosus (LES) (22, 10.09%), ankylosing spondylitis (14, 6.42%), psoriatic arthropathy (12, 5.5%), antiphospholipid antibody syndrome (APS) (10, 4.59%). Maternal age at conception was 34 years (range 18.3–45.7); 19 patients underwent medically assisted reproductive techniques. The most frequent obstetric complications were fluximetric changes, premature rupture of membranes, hypertension and related disorders, gestational diabetes, hypothyroidism and intrauterine growth retardation. The average gestational age at delivery was 38.24 weeks (range 26.71–41.29) with higher frequency of prematurity in patients with APS (55%), LES (39%) and UCTD (19%), as well as in the two pregnancies of patients with mixed connective tissue disease and systemic sclerosis. The comparison between favourable outcomes of prospective versus anamnestic pregnancies showed a significant difference (p<0.001) for prospectively followed pregnancies, regardless of maternal diagnosis. Conclusions: Pre-conception counselling and close multidisciplinary follow-up during pregnancy are essential for a better maternal-fetal outcome in patients with rheumatic diseases. References: [1] Spinillo A, Beneventi F, Locatelli E, et al. The impact of unrecognized autoimmune rheumatic diseases on the incidence of preeclampsia and fetal growth restriction: a longitudinal cohort study. BMC Pregnancy Childbirth2016. [2] Østensen M, Andreoli L, Brucato A, et al. State of the art: Reproduction and pregnancy in rheumatic diseases. Autoimmun Rev2015. [3] Tincani A, Dall'Ara F, Lazzaroni MG, et al. Pregnancy in patients with autoimmune disease: A reality in 2016. Autoimmun Rev2016. Disclosure of Interest: None declared